Penggunaan Pendekatan Kontekstual dalam Meningkatkan Aktivitas Belajar - Marselina Jehumul; Yuliani Sepe Wangge; Ainun Jariyah (Journal of Elementary School (JOES), 2018)
The study aims at knowing the improvement of students science activities through contextual approach at grade V in SDK Colol II Manggarai regency. The study was a classroom action research (CAR). The subject of the study was grade V consist of 19 students. The methods to collect the data were observation, interview and documentation. The data were analyzed through qualitative descriptive method. The result was, based on the analysis, learning achievement in cycle I was 60,08% in category 'quite active'. Then it was improved in cycle II to 88,8% with category 'very good'. In conclusion, the application of contextual approach can improve students learning activities. Keywords: Learning Activities, Contextual Approach